Comparison of the inhibitory effect of the alcoholic extract of pomegranate peel and antibiotics against some intestinal bacterial isolates - A. Aziz, Raghad (Iraqi Journal of Science, 2023)
This research included isolation of 18 bacterial isolates from children stool with diarrhea and acute bloody water and under the age of five, if possible get a 9 isolates of the bacterium Escherichia coli and 5 isolates of the bacterium Salmonella typhimurium and 4 isolation of the bacterium Shigella flexneri, subjected all of these isolates tests AGRO and microscopic and biochemical and diagnosed using Vitek2 system. Tested the effectiveness of inhibitory extract alcohol to peel pomegranate Punica granatum L. in the growth of isolates bacterial intestinal and using the diffusion method in drilling Well diffusion as well as determine the focus damper Near Minimum inhibitory concentration MIC and focus killer Near Minimal bactericidal concentration MBC extract against these isolates bacterial, showed alcoholic extract of the peel pomegranate a clear impact on all isolates bacterial intestinal and this effect compared with the effect of 10 antibiotics included (Rifampicin, Amoxicilln, Ampicillin, Ciprofloxacin, Trimethoprim, Cefotaxim, Ceftriaxon, Neumycin, Tetracyclin, Chloramphenicol). Inhibitory effect of the alcoholic extract of peel pomegranate has been getting increasing with the concentration of extract, as the focus value of damper minimum MIC and focus killer Near MBC extract against all of the bacteria Escherichia coli and bacteria Shigella flexneri were 1 and 2 mg / ml, respectively, while the damper minimum focus MIC extract value against bacteria Salmonella typhimurium is 2 mg / ml while the killer is not specified minimum value of MBC focus extract against these bacteria